Variations in the photosynthetic performance along the leaves of the tropical seagrass Thalassia testudinum - ENRIQUEZ, S; MERINO, M; IGLESIAS-PRIETO, R (Marine biology, 2002)
We examined the role of irradiance in the regulation of photosynthetic performance in a dense (1700 shoots m super(-2)) population of the seagrass Thalassia testudinum Banks ex Koenig exposed to high irradiance and low nutrient availability, located in the Mexican Caribbean. The results indicate that leaf self-shading strongly modifies the light environment within the seagrass canopy. An individual leaf section experiences, during leaf elongation, a photon flux density gradient that changes by three orders of magnitude. This variation leads to site-specific photosynthetic performance, not predictable from descriptions of the optical characteristics of the water column above the canopy. Reductions in pigment content and leaf absorptance towards the apical regions of the second youngest leaf were accompanied with permanent reductions in the quantum yield of photosystem II (F sub(v)/F sub(m)) as a consequence of an accumulation of inactive reaction centers ("chronic photoinhibition"). These changes were strongly associated with the number of hours that a particular leaf section is exposed to supersaturating irradiance, but are not indicative of photoinhibition sensu stricto, as we did not find any significant difference in the photosynthetic response of basal and apical leaf sections to increasing irradiance. Apical leaf sections experienced a fivefold midday reduction in F sub(v)/F sub(m) compared with the small but significant reduction shown by basal sections. It is highly probable that incomplete diurnal recovery of the light-dependent midday F sub(v)/F sub(m) reduction ("dynamic photoinhibition") causes the observed age-dependent F sub(v) /F sub(m) loss experienced by T. testudinum leaves. Comparison of the estimates of integrated daily production from physiological data indicate a dramatic overestimation of daily production by the values obtained using only optical characteristics of the water column and excluding light attenuation within the canopy.